Monogami dalam Perjanjian Perkawinan (Kajian Hukum Islam dan Perundang-undangan di Indonesia) - Istianah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2019)
This paper discusses monogamy as a material in marriage agreements according to Islamic law and legislation. The focus of the study is on the rules regarding marriage agreements and monogamy as material in marriage agreements in Islamic law and legislation in Indonesia. The method used is normative juridical. Sources of legal materials, namely: Al-Qur’an, Hadith, classical fiqh, Civil Code, Republic of Indonesia Law Number 16 of 2019 Regarding Amendments to Law Number 1 of 1974 concerning Marriage and Presidential Instruction Number 1 of 1991 concerning Islamic Legal Compilation. Technical analysis using prescriptive analysis. The results showed that marriage agreements in Islamic law are permissible if they do not conflict with Islamic law. Marriage agreements are also regulated in the Civil Code, Marriage Law and KHI, where marriage agreements are permitted if they do not conflict with decency, legislation and public order. Monogamy as a material in a marriage agreement is permissible in Islamic law and has a normative reference in the Qur'an, Hadith and fiqh scholars. Laws and regulations in Indonesia also provide opportunities regarding monogamy which can be used as material for marriage agreements, even wives can require monogamy as taklik talak.